Connections of the zona incerta to the reticular nucleus of the thalamus in the rat - ONAT, FİLİZ; YANANLI, HASAN RACİ; GÜLHAN, REZZAN (WILEY, 2006)
This study demonstrated that there is a pathway from the zona incerta to the thalamic reticular nucleus. Injections of horseradish peroxidase or Fluorogold were made, using stereotaxic coordinates, into the rostral, intermediate or caudal regions of the thalamic reticular nucleus of adult Sprague-Dawley rats. The results show that the different regions of the thalamic reticular nucleus have distinct patterns of connections with the sectors of the zona incerta. In terms of the relative strength of the connections, injections made into the rostral regions of the thalamic reticular nucleus showed the highest number of labelled cells within the rostral and ventral sectors of the zona incerta; injections made into the intermediate regions of the thalamic reticular nucleus showed labelled cells in the dorsal and ventral sectors; while injections to the caudal regions of the thalamic reticular nucleus showed only a few labelled cells in the caudal sector of the zona incerta. Previous studies have shown that the zona incerta projects to the higher order thalamic nuclei but not first order thalamic nuclei. The labelling observed in the present study may represent collaterals of zona incerta to higher order thalamic nuclei projections.
Keywords: connections; thalamic reticular nucleus; zona incerta; SUPERIOR COLLICULUS; HORSERADISH-PEROXIDASE; VISUAL SECTOR; BRAIN-STEM; ORGANIZATION; PROJECTION; NEURONS; AFFERENTS; LESIONS